2018
DOI: 10.4172/2375-4397.1000214
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Method for the Monitoring of Environmental Benzene at Low Concentration Using the Needle Trap Device

Abstract: a headache, drowsiness, nausea, dizziness, confusion, severe damage to the kidney, the liver and the nervous system, and the irritation of the nose were reported [12-15]. Acute exposure through inhalation can cause illnesses such as headaches, drowsiness, dizziness, and irritation of the skin, whereas chronic exposure may cause more severe ailments, including aplastic anemia and leukemia at the occupational settings [16,17]. Due to its potential health threats, in according to the International Agency for Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Sousa et al studied benzene levels in indoor and outdoor environments using the GC-FID technique, with tandem mass spectrometric detection (MS/MS) used to confirm benzene in ambient air [ 96 ]. Bayatian et al reported a new method involving a sampling needle trap device (NTD) and analysis performed using GC-FID, with benzene level measured in the range of 0.15 to 1.2 ppm [ 97 ]. Kumari et al reported benzene concentrations at fuel stations and traffic intersections, with sampling conducted using charcoal sorbent tubes and subsequent analysis using GC-FID [ 2 - 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sousa et al studied benzene levels in indoor and outdoor environments using the GC-FID technique, with tandem mass spectrometric detection (MS/MS) used to confirm benzene in ambient air [ 96 ]. Bayatian et al reported a new method involving a sampling needle trap device (NTD) and analysis performed using GC-FID, with benzene level measured in the range of 0.15 to 1.2 ppm [ 97 ]. Kumari et al reported benzene concentrations at fuel stations and traffic intersections, with sampling conducted using charcoal sorbent tubes and subsequent analysis using GC-FID [ 2 - 3 ].…”
Section: Methodsmentioning
confidence: 99%